2021
DOI: 10.1007/s11357-021-00385-3
|View full text |Cite
|
Sign up to set email alerts
|

Increased procoagulant platelet levels are predictive of death in COVID-19

Abstract: Prior research has identified abnormal platelet procoagulant responses in COVID-19. Coated-platelets, a form of procoagulant platelets, support thrombin formation and are elevated in ischemic stroke patients with increased risk for recurrent infarction. Our goal was to examine changes in coated-platelet levels over the course of COVID-19 infection and determine their association with disease severity, thrombosis, and death. Coated-platelet levels were assayed after admission and repeated weekly in COVID-19 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Anti-PS antibodies correlated with high levels of platelets. Although a low platelet count is associated with increased risk of severe disease and mortality in patients with COVID-19 (Lippi et al, 2020), it has also been observed that platelets are hyperactivated during the disease (Zaid et al, 2020) and that immature platelets (Welder et al, 2021) and coated-platelet levels (Khattab et al, 2021) correlate with severity and death in COVID-19 patients, suggesting that they may be involved in thrombo-inflammation and contribute to disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-PS antibodies correlated with high levels of platelets. Although a low platelet count is associated with increased risk of severe disease and mortality in patients with COVID-19 (Lippi et al, 2020), it has also been observed that platelets are hyperactivated during the disease (Zaid et al, 2020) and that immature platelets (Welder et al, 2021) and coated-platelet levels (Khattab et al, 2021) correlate with severity and death in COVID-19 patients, suggesting that they may be involved in thrombo-inflammation and contribute to disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, since Ca 2+ influxes are important to trigger the procoagulant response, physiological levels of Ca 2+ are required in the medium [ 45 , 46 ]. Nowadays, convulxin/thrombin (COAT) dual agonist stimulation in Ca 2+ buffer—generally recognized as standard—is extensively used by many research groups to assess procoagulant function of platelets [ 3 , 4 , 12 , 22 , 47 , 48 , 49 , 50 , 51 ]. Common model such as procoagulant COAT platelets are required in order to compare observations between research groups [ 51 ].…”
Section: Procoagulant Platelet Characterizationmentioning
confidence: 99%
“…This balance seems to be altered in bleeding diatheses [ 6 , 7 ] and hemorrhagic strokes [ 8 , 9 ] where a low procoagulant potential has been observed. On the other hand, in ischemic strokes [ 10 , 11 ] and in conditions as diverse as COVID-19 [ 12 ] and coronary artery disease [ 13 ], a high procoagulant potential was associated with a worse outcome. The clinical implications of procoagulant COAT platelets are addressed in a recent review [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the impact of COVID-19 on prothrombotic and procoagulatory platelet function is multifaceted, and the underlying molecular mechanisms remain largely obscure. Although high levels of procoagulant fibrinogen-binding platelets, so-called coated platelets, are predictive of death in COVID-19, most patients exhibit lower levels of coated platelets than hospitalized SARS-CoV-2-negative controls ( 24 ). In line, despite the reported association of platelet PS expression with thrombosis and disease severity, the capacity of platelets to respond to stimulation is reduced in COVID-19 ( 25 ).…”
Section: Introductionmentioning
confidence: 99%